Quasi-Steady State Solutions of MHD Oscillatory Flow Between two Parallel Plates in a Rotating System - Rani, CH. Baby (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The physical situation considered is that of quasi-state hydro magnetic flow of a viscous, incompressible and electrically conducting fluid between two parallel plates distance™ apart, when the lower plate is set in sinusoidal motion and the upper stationary .Neglecting the Magnetic Prandtl Number, Solution for Quasi-study state when the lower plate moves with cos ( and the corresponding Skin friction at the lower plate have been obtained. Discussion has been made of these two features for the two cases when the magnetic lines of force have been fixed relative to the fluid and the moving plate respectively.